PENGARUH KEPEMIMPINAN, BUDAYA ORGANISASI, LINGKUNGAN KERJA TERHADAP KEPUASAN KERJA PADA PEGAWAI KANTOR BADAN PENANGGULANGAN BENCANA DAERAH KABUPATEN KERINCI - Yanita, Poni (Jurnal Benefita, 2017)
The research is proposed to the influence of leadership, organizational culture and work environment to job satisfaction to civil servants Disaster Agency Kerinci Regency. The population in this research were to civil servants Disaster Agency Kerinci Regency. The population in this research were  civil servants Disaster Agency Kerinci Regency size of 68 people . Furthermore, by using the formula Slovin, then elected a sample size of 58 servants Disaster Agency Kerinci Regency with sample tecnique is used namely Simple Random Sampling. The data which namely primer data and skunder data used in this research. For analyzing data by using multiple linear regression analysis and research hipothesis by using testing t with SPSS version 20 is used to analyze the data. The analyze result shows that the leadership, organizational culture and work environment to cause the positive and significant to job satisfaction.